Using routinely collected laboratory and health administrative data to assess influenza vaccine effectiveness: introducing the Flu and Other Respiratory Viruses Research (FOREVER) Cohort - Jeff Kwong; Sarah Buchan; Hannah Chung; Michael Campitelli; Kevin Schwartz; Natasha Crowcroft; Michael Jackson; Timothy Karnauchow; Kevin Katz; Allison McGeer; Dayre McNally; David Richardson; et al. (International Journal of Population Data Science, 2018)
Introduction Annual evaluation of influenza vaccine effectiveness (VE) is required because of frequent changes to circulating and vaccine strains. Traditionally, VE studies enroll patients who fulfill case definitions for respiratory infections and are tested for influenza. VE estimates generated from convenience samples of routinely collected specimens might be biased.